2020
DOI: 10.1007/s11581-020-03713-3
|View full text |Cite
|
Sign up to set email alerts
|

High power density supercapacitor devices based on nickel foam–coated rGO/MnCo2O4 nanocomposites

Abstract: New nanocomposite electrode material of rGO/MnCo 2 O 4 was freely loaded on flexible substrate on nickel foam and prepared by a simple, cost-effective, and eco-friendly pathway. The results show that the spinel manganese cobaltite (MnCo 2 O 4) with reduced graphene oxide (rGO) nanocomposite forms a uniform deposit and densely covers on the nickel foam (NF). The electrochemical measurements were investigated in three methods, such as cyclic voltammetry (CV), galvanostatic charge/discharge (GCD), and electrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 84 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Various hypotheses have been proposed to explain the origin of the capacitance increase of graphene electrodes while performing voltage and current scans. [6,7,47] Yadav et al [6] studied N-doped rGOs and suggested that the increase in specific capacitance may have resulted from the deposition of dissolved Pt content from the counter electrode or the electrochemical activation of the graphene's functional groups with the conducted scans. Another relevant study that focused on electrochemical functionalization showed that exceeding a certain anodic voltage limit of CV scans increases the graphene's specific capacitance and the reason was explained as additional defect formation based on variation of XPS measurements taken before and after the experiments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Various hypotheses have been proposed to explain the origin of the capacitance increase of graphene electrodes while performing voltage and current scans. [6,7,47] Yadav et al [6] studied N-doped rGOs and suggested that the increase in specific capacitance may have resulted from the deposition of dissolved Pt content from the counter electrode or the electrochemical activation of the graphene's functional groups with the conducted scans. Another relevant study that focused on electrochemical functionalization showed that exceeding a certain anodic voltage limit of CV scans increases the graphene's specific capacitance and the reason was explained as additional defect formation based on variation of XPS measurements taken before and after the experiments.…”
Section: Resultsmentioning
confidence: 99%
“…[7] The increased wettability of the electrode surface also proposed as a possible explanation. [47] In this study, the electrodes were kept in DI water for a day before the measurement and the PBS electrolyte used on the measurements will not cause Pt dissolution. Therefore, the electrochemical functionalization of graphene and the separation of stacked graphene sheets by the applied voltage are the most likely explanations for the increase in specific capacitance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations